Structural Equation Modeling of the Relationship Between Parents’ Religious Orientation and Adolescents’ Tendency Towards Critical Thinking and Happiness with the Mediating Role of Cognitive Flexibility - Eshagh Neymvari, Neda; Abolghasemi, Shahnam; Hamzeh Poor Haghighi, Tahereh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to determine the model fit based on the relationship between parents’ religious orientation and the tendency towards critical thinking and happiness with the mediating role of cognitive flexibility in female high school students. Method: This descriptive correlational study was conducted with a population of teenage girls from public high schools in the city of Chalus. A sample of 319 participants was selected using cluster random sampling. Data collection tools included the Ricketts Critical Thinking Questionnaire (2003), the Dennis and Vander Wal Cognitive Flexibility Inventory (2010), the Allport and Ross Religious Orientation Questionnaire (1967), and the Oxford Happiness Inventory (Argyle et al., 1989). Findings: Results showed a significant positive relationship between religious orientation and critical thinking tendency (r = 0.45, p < 0.05), happiness (r = 0.41, p < 0.05), and cognitive flexibility (r = 0.68, p < 0.05). There was also a significant positive relationship between cognitive flexibility and the tendency towards critical thinking (r = 0.73, p < 0.01) and happiness (r = 0.69, p < 0.01). Conclusions: Based on the results of structural equation modeling, the model based on the relationship between parents’ religious orientation and the tendency towards critical thinking and happiness with the mediating role of cognitive flexibility among students is adequately fitted. The application of promoting religious duties and training in cognitive flexibility to enhance happiness and critical thinking tendency in students could be considered in experimental studies by researchers, educational planners, and counselors.